Hot desert soils—Global distribution and unique characteristics - Khormali, Farhad; Monger, Curtis (Geoderma Regional, 2020)
Hot desert soils occur on every continent as places with wildland, scientific, aesthetic, and cultural value. Where perennial sources of water have existed in history, like the Nile, hot deserts were environment where early human civilizations arose across the world. Hot deserts are also important reservoirs of inorganic carbon, sources of local and intercontinental dust, and grazing habitat. Desert soils having paleo-features are also important in view of the paleoenvironmental reconstruction. “Non-flushing” soil profiles leading to the accumulation of soluble salts, gypsum, and carbonates is the dominant feature of hot desert soils. Other unique features include desert pavements, varnish, and biocrusts. Biocrusts not only fix nitrogen, influence runoff, and protect soils from wind erosion, they also play a role in biomineralization of carbonate. Pedogenic studies of hot desert soils are providing a better understanding of fundamental physical, chemical, and biotic/abiotic interactions in one of the most extreme environments on Earth, an understanding that may provide insight on extreme environments elsewhere in the universe, like Mars. •Hot desert soils are a member of soil types formed in an extreme environment on Earth.•Hot desert soils are “non-flushing” soils that accumulate soluble constituents in their profiles.•Accumulation of soluble salts, gypsum, and carbonates, and desert pavements, varnish, and biocrusts are the main features.•Pedogenic studies of hot desert soils provide a better understanding of physical, chemical, and biotic/abiotic interactions.